Environmental policy in Hungary - Enyedi, György; Zentai, Viola (Discussion Papers, 1986)
It was only in the late 1960s that an overall policy for environmental protection started to develop in Hungary. The formulation of an environmental policy was made necessary by the rapid deterioration of the environment in countries with highly developed industry. In Hungary, this era was characterized by prosperity and a rapid rise in the living standard. This was the first time that the rapid economic development was restricted by the environment, first of all, by the scarcity of water. After reviewing the historical background of environmental policy and legislation, the author presents the management and organizational structure of environmental protection. The third chapter deals with the environment decision-making process, and introduces the main actors of environmental protection (the state, the producers, the local councils and finally the citizens). In the final section, the author discusses the obstacles to the implementation of environmental protectional purposes.